1999
DOI: 10.1080/00071669986945
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced oviposition delays in laying hens: Duration and consequences for eggshell quality

Abstract: 1. As part of a programme investigating the causation of pecking damage in fowls, this experiment tested a proposal that birds may receive more feather pecks when their plumage colour contrasts with floor litter colour, because litter particles on plumage (as a consequence of dustbathing) may then have greater stimulus value. 2. Groups consisting of 7 light- and 7 dark-coloured bantams were reared from 1 to 11 weeks of age in pens with either wood shavings (light coloured, n=6) or peat (dark coloured, n=6) flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 22 publications
0
36
0
Order By: Relevance
“…They were provided with full verbal and written instructions on how to complete the forms and a set of photographic scales for standardising scores of variables such as feather damage. Under conditions of stress, hens sometimes delay laying eggs which results in additional calcium carbonate being deposited on the egg shell or egg shell deformations (Hughes et al, 1986;Mills et al, 1987;Reynard and Savory, 1999). In addition, if the hen's vent prolapses or is torn due to laying an overly large egg, this can sometimes result in blood stains being visible on the shells.…”
Section: Data Collected By Producersmentioning
confidence: 95%
“…They were provided with full verbal and written instructions on how to complete the forms and a set of photographic scales for standardising scores of variables such as feather damage. Under conditions of stress, hens sometimes delay laying eggs which results in additional calcium carbonate being deposited on the egg shell or egg shell deformations (Hughes et al, 1986;Mills et al, 1987;Reynard and Savory, 1999). In addition, if the hen's vent prolapses or is torn due to laying an overly large egg, this can sometimes result in blood stains being visible on the shells.…”
Section: Data Collected By Producersmentioning
confidence: 95%
“…Zupan et al (2008a) observed that layers that do not have access to suitable nest sites may present an elaborate sequence of nest seeking and building behaviors one hour before lay, with apparent frustration signs, such as excessive locomotion and exploratory activities (Cooper & Appleby, 1996), as well as a special vocalization, called gackel-call (Zimmerman et al, 2000). In addition, frustration may be physiologically expressed by egg retention in the eggshell gland (Hughes et al, 1986), resulting in an extra calcium layer on the eggshell (Reynard & Savory, 1999). According to Keeling (2004), these signs indicate that the hen's welfare was compromised by the lack of a suitable nest.…”
Section: Nestingmentioning
confidence: 99%
“…The negative effect of higher temperature on time of oviposition in laying hens could be considered as an environmental stressor which, according to Hughes et al (1986) and Reynard and Savory (1999), can delay oviposition. Also Yoshida et al (2011) suggested a possible effect of heat stress on ovarian function and consequently egg production in laying hens.…”
Section: Resultsmentioning
confidence: 99%